Propuesta de un Plan de Comunicación Política para Unificar y Fortalecer la Identidad Visual e Imagen de la Asambleísta Lourdes Tibán en Redes Sociales - Vinueza Chávez, Claudia Lizeth (2015)
National assemblywoman Lourdes Tibán is highly regarded and popular among citizens; her personality and her career in politics, has made her figure strong and now she has a place in the national assembly. Her work, image and political performance is only known to part of Quito citizens mainly due to lack of knowledge regarding the activities, projects, laws end reforms in which she is involved. Consequently, people have erroneous criteria, perceptions and points of view regarding her public governance as Assemblywoman and political figure. In order to strengthen her political image, Lourdes Tibán should create and maintain links with her target audiences, encourage citizen interaction and participation in whatever is related with her tenure. This thesis has seven chapters. A proposal for a political communication plan through the social networks in order to unify and strengthen the visual identity and image of the Assemblywoman Lourdes Tibán is made upon a thorough theoretical research and with the analysis of the current situation The first chapter deals with the political communication starting from her history, definitions, processes and applications. The second chapter, refers to the political image, concept, classification, construction, image crisis, crisis prevention, crisis manual and finally public opinion study. The third chapter discusses everything about Visual Identity, definition, components, importance, visual identity manual and also makes reference to the brand concept in politics. The fourth chapter discusses internet, digital tools web 2.0 and social networks that can be adapted to political communication. Campaigns, leadership and reputation 2.0 and their impact nowadays will also be discussed. The fifth chapter corresponds to Dra. Lourdes Tibán, her biography, her long career in politics, current performance as a national assemblywoman, political management and communication tools she handles. The sixth chapter corresponds to qualitative and quantitative research. Surveys and interviews to target audience will allow diagnosis and analysis of the perception that Quito citizens have regarding the image and visual identity of the assemblywoman. The management of digital tools and social networks used during the last six months is also analyzed. The seventh and last chapter proposes a political communication plan in order to correct and improve the image problems that have been ascertained. It further proposes an adequate management of digital tools and social networks. It will end with a listing of conclusions and recommendations.